1991
DOI: 10.1007/bf02050355
|View full text |Cite
|
Sign up to set email alerts
|

Physiologic and anatomic assessment of patients with rectocele

Abstract: Clinical, physiologic, and anatomic assessments were carried out in 22 female patients with symptomatic rectocele (Group A), 15 patients with asymptomatic rectocele (Group B), and 14 subjects having no rectocele (Group C). Resting and pressure, rectal pressure, rectal compliance, anorectal inhibitory reflex, and rectal sensation did not differ among the groups. Proctography revealed that the lengths of the rectocele during attempted defecation in groups A (1.6 [1.0-3.5] cm) (median and range) and B (1.6 [1.0-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
50
2
9

Year Published

1998
1998
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(69 citation statements)
references
References 14 publications
8
50
2
9
Order By: Relevance
“…rectocele. Our study sup- ports the findings of previous research showing no association between bowel dysfunction and stage of POP [15][16][17] and that there are no major physiological differences by AFT between patients with symptomatic rectocele, asymptomatic rectocele and patients without rectocele [18,19] . Our study could not confirm the finding by Siproudhis et al [20,21] , who reported that constipation in patients with rectocele may be related to higher rectal volumes.…”
Section: Discussionsupporting
confidence: 74%
“…rectocele. Our study sup- ports the findings of previous research showing no association between bowel dysfunction and stage of POP [15][16][17] and that there are no major physiological differences by AFT between patients with symptomatic rectocele, asymptomatic rectocele and patients without rectocele [18,19] . Our study could not confirm the finding by Siproudhis et al [20,21] , who reported that constipation in patients with rectocele may be related to higher rectal volumes.…”
Section: Discussionsupporting
confidence: 74%
“…28 Rectocele in females has been associated with a high incidence of perineal descend confirmed by the present report. 29,30 Again, excessive and repeated straining increases the probability of perineal descend and the formation of rectocele.…”
Section: Discussionmentioning
confidence: 99%
“…Rectocele was de¢ned as a bulging of the anterior rectal wall into the lumen of the vagina exceeding 2 cm in size [Shorvon et al, 1989].The size was measured from an extended line of the anal canal to the tip of the rectocele [Yoshioka et al, 1991]. Abnormal pelvic £oor descent was de¢ned as a lowering of the perineal outline exceeding 2 cm at straining [Bremmer et al, 1995].…”
Section: Radiological Examinationmentioning
confidence: 99%